Amino-functionalized CoFe2O4 magnetic nanoparticles as an efficient heterogeneous catalyst for benzaldehyde cyanosilylation - Son Nam et al, Phan Thanh (Vietnam Journal of Chemistry, 2014)
Diaminosilane-functionalized cobalt spinel ferrite (CoFe2O4) magnetic nanoparticles were synthesized and used as an efficient heterogeneous base catalyst for the cyanosilylation reaction benzaldehyde with trimethylsilyl cyanide. The magnetic nanoparticle catalyst was characterized by X-ray powder diffraction (XRD), transmission electron microscope (TEM), thermogravimetric analysis (TGA), fourier transform infrared (FT-IR), nitrogen physisorption measurements. Quantitative conversion (>99%) was achieved under mild conditions. Recovery of catalyst was facilely achieved by magnetic decantation. The supported catalyst could be reused without significant degradation in catalytic activity.